APLIKASI TEKNOLOGI INOVASI PUPUK ORGANIK CAIR BIO-INOKULUM PLUS GUNA PENINGKATAN PERTUMBUHAN DAN PRODUKSI TANAMAN - I Wayan Sunada; Eko Hary Agustin Juwaningsih (Politeknik Pertanian Negeri Kupang, 2019)
Good organic fertilizer is fertilizer that can be used to improve physical, chemical and biological soil properties, and is certified based on laboratory tests and meets fertilizer quality standards. Liquid organic fertilizer Bio-Inoculum Plus is an alternative fertilizer as a result of innovation technology that meets the quality standards of liquid organic fertilizer with a dual function as fertilizer, growth regulators as well as biopesticides. Because it contains complete nutrients (such as organic C, N, P, K, Fe, Mn, Cu, Zn, B, Co and Mo); ZPT (such as Auxin (IAA), GA3, Cytokinins (Kinetin and Zeatin)) and also contain Azospirilium sp. Microbes, Pospate Solvent Bacteria (Bacillus sp and Pseudomonas sp), Actinomycetes sp, Trichoderma sp and Beauveria bassiana. The results obtained from the application of liquid organic fertilizer Bio-Inoculum on the propagation of fruit plants using cuttings to sprout shoots and roots take between 7-18 days. To accelerate plant growth, accelerate flowering and fruiting on plants that are difficult to grow flowers and fruit. That can replace the role of inorganic fertilizers and plant growth to be more fertile, healthier and increase crop yields by 15-30%. Keywords: Application of Organic Agriculture, Bio-Inoculum Liquid Organic Fertilizer, Propagation of Plant Cuttings, Accelerating Flowering and Fertilization, Increasing Production.